Partial molar ectopic pregnancy: A case report - Malihe Amirian; Malihe Hasanzadeh; Leili Hafizi (Mashhad University of Medical Sciences, 2016)
Partial or complete mole affects one in 1000  pregnancies.Partial mole is a rare form of ectopic pregnancy. There was a married woman,gravid 4,parity 1,abortion 1,and she had past medical history 0f right ectopic pregnancy.she had left ectopic pregnancy and was treated by laparascopic left salpyngectomy after failure of intramascular methotrexate treatment.After surgery  the pathology exam showed partial mole